2018
DOI: 10.3390/nu10081044
|View full text |Cite
|
Sign up to set email alerts
|

Mexican Households’ Purchases of Foods and Beverages Vary by Store-Type, Taxation Status, and SES

Abstract: Where people shop for food is often linked to the healthiness of food purchases. In Mexico, no research has examined the connection between where people shop, what they buy, and their socioeconomic status (SES). Mexico’s sugary beverage and junk food taxes have made households decrease purchases of taxed products. However, whether households have changed where they shop is unknown. To address this gap, we use a repeated cross-sectional analysis of household packaged food and beverage purchases from the Nielsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 33 publications
7
33
0
1
Order By: Relevance
“…Consistent with previous studies using the Mexico Nielsen CPS data, SES was categorized into low, middle and high. The SES index is comprised of seven household assets (number of rooms, type of floor, number of bathrooms, shower, gas range, number of light bulbs and number of cars), and the education level of the head of the household [9, 11, 15, 19, 20].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistent with previous studies using the Mexico Nielsen CPS data, SES was categorized into low, middle and high. The SES index is comprised of seven household assets (number of rooms, type of floor, number of bathrooms, shower, gas range, number of light bulbs and number of cars), and the education level of the head of the household [9, 11, 15, 19, 20].…”
Section: Methodsmentioning
confidence: 99%
“…Because food suppliers are major mediators between the food environment and the eating behaviors that influence the development of obesity [13, 14], determining whether calories and sugars from beverages vary by store-type is important. Evidence has shown that the types of beverages that Mexican households purchase vary by store-type and purchases of taxed beverages are highest at traditional stores [15]. Store-level interventions and policies can potentially increase the healthfulness of stores’ assortment of foods and beverages, improve households’ diet quality and prevent obesity [1618].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…traditional shops (small family-owned shops, e.g. bodegas, tiendas, momand-pop shops) and supermarkets) and found variations observed by socio-economic status (SES) (28) . These variations included low-SES households purchasing primarily at traditional retailers and middle-and high-SES households primarily at supermarkets.…”
mentioning
confidence: 99%